2011 Workshop on Predictive Control of Electrical Drives and Power Electronics 2011
DOI: 10.1109/precede.2011.6078687
|View full text |Cite
|
Sign up to set email alerts
|

Design choices for the prediction and optimization stage of finite-set model based predictive control

Abstract: Abstract-The interest in applying model-based predictive control (MBPC) for power-electronic converters has grown tremendously in the past years. This is due to the fact that MBPC allows fast and accurate control of multiple controlled variables for hybrid systems such as a power electronic converter and its load. As MBPC is a family of possible controllers rather than one single controller, several design choices are to be made when implementing MBPC. In this paper several conceptual possibilities are conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…For digital control we found that the most important control techniques are implemented in FPGAs, like fuzzy control [1499][1500][1501][1502], PID [69,1503,1504], model predictive control [73,76,1505], adaptive control [80,81,1506], sensorless control [1507][1508][1509] and distributed control [96,99,101]. These digital control techniques were implemented in FPGAs due the high speed response that a hardware digital control FPGA-based implementation can achieve and its reconfiguration capability, allowing control application to high speed system such as induction motors [1507,[1510][1511][1512], torque control [75,1513,1514], Brushless DC (Direct Current) motors [1515][1516][1517], current control [1518,1519], among others [65,[1520][1521][1522][1523].…”
Section: Discussionmentioning
confidence: 99%
“…For digital control we found that the most important control techniques are implemented in FPGAs, like fuzzy control [1499][1500][1501][1502], PID [69,1503,1504], model predictive control [73,76,1505], adaptive control [80,81,1506], sensorless control [1507][1508][1509] and distributed control [96,99,101]. These digital control techniques were implemented in FPGAs due the high speed response that a hardware digital control FPGA-based implementation can achieve and its reconfiguration capability, allowing control application to high speed system such as induction motors [1507,[1510][1511][1512], torque control [75,1513,1514], Brushless DC (Direct Current) motors [1515][1516][1517], current control [1518,1519], among others [65,[1520][1521][1522][1523].…”
Section: Discussionmentioning
confidence: 99%
“…The standard PI-MPTC method uses torque and stator flux to form a cost function by using weighting factors to determine the optimal voltage vector for the next sampling time [21,22]. The weighting factor is affected by the system parameters [23], so the weighting factor setting is generally more complicated. In addition, the weighting factors have a great impact on the performance of the controller, because they balance the torque and stator flux effects on the system.…”
Section: Traditional Model Predictive Torque Controlmentioning
confidence: 99%
“…The weighting factors are used to tune the importance or cost of a particular target in relation to the other control targets. Different strategies using online and offline search procedures have been proposed in [20], [21], which are strongly dependent on system parameters and require a comprehensive mathematical analysis. Moreover, when the desired control objectives are more than two, trial and error methods are used running computer simulations, which are extremely time consuming [22]- [24].…”
Section: Introductionmentioning
confidence: 99%